Regression analysis of motivation factors for paying a Zakat to strengtheness of Ummah in Kolaka Regency - Muhammad Askari Zakariah; Muhammad Zakariah; Irma Suciana; Hikmawati Hikmawati; Reza Setiawan; Sultan Sultan; Abdul Haris Nasution (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The objective of this study was to identify a motivation of Muzakki (as payer a zakat) for paying a zakat. The experiment was conducted at Kolaka district from January to February 2017. This research was used 3 factors, satisfied (X1), served (X2), and Islamic knowledge (X3) to motivation of muzakki (Y). Data were analyzed by regression analysis. The result showed that value of R was 95,6%, it was indicated that factor formulation was valid to identify motivation of Muzakki for paying zakat. One way analysis of varians showed a significant. Formula of regression analysis was Y= -0.36+1,12X1+1,054X2+0.924X3. Value of constant -0.36 was indicated that without three factors would be negative motivation or nothing motivation to be paid a zakat. Satisfied was highest factor could be influenced motivation to be paid a zakat by Muzakki. In fact, that Islamic knowledge was lowest factor. Research could be concluded that satisfied of muzakki was highest factor affected to motivation for paying zakat. Amil (as collector of zakat for distribution to mustahiq) should be credible, liable to service, and trustworthy for building of good satisfied of Muzakki.